The Influence of Communication Through Social Media on Brand Equity in Shaping Nike Product Purchase Intentions - Rafi Wahyu Perdana; Raden Roro Ratna Roostika (Pusat Publikasi Nusantara, 2023)
The development of social media indicates a new trend where companies use social media for communication and product promotion. By utilizing social media, companies can interact with consumers, making social media communication created by companies an essential element of the company's promotional mix (Poulis et al., 2018). The purpose of this study is to determine the influence of social media communication on brand equity and brand attitude in shaping the purchase intention of Nike products. This research employs Structural Equation Modeling (SEM) analysis with the assistance of AMOS software, involving a total sample of 223 respondents. The results of this study show that firm-created content and user-generated content have a positive impact on brand equity. User-generated content has a positive effect on brand attitude, while firm-created content does not have a positive effect on brand attitude. Furthermore, brand equity and brand attitude have a positive impact on purchase intention. This study reveals that user-generated communication has a more significant influence on purchase intent through brand equity and brand attitude. Brand equity and brand attitude are crucial factors in the purchase intention of a product.